Simultaneous determination of multiple active 2‐(2‐phenylethyl)chromone analogues in agarwood by HPLC, QAMS, and UPLC‐MS. Issue 3 (16th September 2020) - Gao, Mei; Han, Xiaomin; Huang, Junqing; Sun, Ying; Liu, Yangyang; Chen, Hongjiang; Jin, Yue; Yang, Yun; Gao, Zhihui; Xu, Yanhong; Zhang, Zheng; He, Chunnian
Abstract: Introduction: Chromones are the major constituents of agarwood and are considered to be directly related to its quality. Agarotetrol, a chromone derivative, is a Chinese Pharmacopoeia content detection index. However, comprehensive high‐performance liquid chromatography (HPLC), quantitative analysis of multiple components by a single marker (QAMS), and ultra‐performance liquid chromatography mass spectrometry (UPLC‐MS) analyses of this pharmacopeial plant material have never been performed. Moreover, reports regarding the separation and detection of multiple active 2‐(2‐phenylethyl)chromone analogues from this plant material are surprisingly scarce. Objective: To establish a simple, reliable, and effective HPLC method utilising both diode array and MS detection for the simultaneous determination of multiple active chromone analogues in agarwood. Methods: Four 2‐(2‐phenylethyl)chromones were isolated from methanol extracts of agarwood. After optimising the extraction, separation, and analytical conditions, validation of the developed analytical method indicated good linearity, satisfactory precision, and good recovery. On this basis, a method for the quantitative analysis of multiple components by a single marker was established. The four 2‐(2‐phenylethyl)chromones were identified by nuclear magnetic resonance spectroscopic analysis and UPLC coupled to electrospray ionisation quadrupole‐time‐of‐flight MS. Conclusions: The behaviour of the chromones characterised by MS fragmentation indicated a loss of molecular CO and the formation of m/z 121 compounds by the cleavage of CH2 ‐CH2 bonds between the chromone and phenyl moieties. Three detection methods were successfully used in this study for agarwood detection, and this protocol may potentially be used as a tool for the quality control of agarwood. Abstract : Chromones are the major constituents of agarwood and are considered to be directly related to its quality. 2‐(2‐phenylethyl)chromones were isolated from methanol extracts of agarwood. To establish a simple, reliable, and effective HPLC method of multiple active chromone analogues in agarwood. The four 2‐(2‐phenylethyl)chromones were identified by nuclear magnetic resonance spectroscopic analysis and UPLC coupled to electrospray ionisation quadrupole‐time‐of‐flight MS.